A curious case of toddler with hernia and much more - Ramu, Abhirup H.; Kenchetty, Priyanka; Chidananda, Aishwarya K. (International Surgery Journal, 2021)
Transverse testicular ectopia (TTE) with fused vas deferens is an extremely rare clinical entity. Herein, we presented a case of a 2 years old patient with left inguino-scrotal swelling associated with pain lasting for 3 days. Clinical examination revealed an empty right hemi-scrotum, a left-sided giant inguino-scrotal swelling. Laboratory tests were normal. Ultrasound imaging (US) of the scrotum demonstrated the presence of both testes in the same left hemi-scrotum with inguinal hernia and enterocele as content. Surgical intervention in suspicion of obstruction was carried out through inguinal incision. There was a congenital inguinal hernia with appendix (type 1-Amyand’s hernia) and cecum as content with two well developed testes on the same side with separate epididymis and vas deferens. Both the testes were united by a mesorchium. Hence, reduction of contents with herniotomy and both the testes were anchored to inner aspect of left thigh one above the other. We reviewed the literature for rare diagnosis of TTE.